Ghana’s Economic and Agricultural Transformation: Past Performance and Future Prospects - Diao, Xinshen; Kolavalli, Shashidara; Resnick, Danielle (2019)
Xinshen Diao, Shashidara Kolavalli, and Danielle Resnick BOOK LAUNCH Ghana’s Economic and Agricultural Transformation: Past Performance and Future Prospects Co-Organized by IFPRI and the CGIAR Research Program on Policies, Institutions, and Markets (PIM) OCT 9, 2019 - 12:15 PM TO 01:45 PM EDT